From monologue to dialogue : radio and reform in Indonesia - Jurriëns, Edwin, 1972- (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 2009)
"From monologue to dialogue; Radio and reform in Indonesia analyses how radio journalism since the late 1990s has been shaped by and contributed to Reformasi, or the ambition of democratizing Indonesian politics, economy and society. The book examines ideas and practices such as independent journalism, peace journalism, meta-journalism, virtual interactivity, talk-back radio and community radio, which have all been designed to renew audience interest in media and societal affairs. It pays special attention to radio programmes that enable hosts, experts, listeners and other participants to discuss and negotiate the very rules and boundaries of Indonesia's newly acquired media freedom. The author argues that these contemporary programmes provide dialogic alternatives to the official New Order discourse dominated by monologism. Edwin Jurriëns is Lecturer in Indonesian Language and Culture at the University of New South Wales, Canberra, Australia. He is author of Cultural travel and migrancy; The artistic representation of globalization in the electronic media of West Java (KITLV, 2004) and co-editor of Cosmopatriots; On distant belongings and close encounters (Rodopi, 2007.)"--Publisher's description.